Wavefront-optimized treatment for myopia using Allegretto Wave Eye-Q excimer laser - Celeste P. Guzman, MD; Jessica Marie R. Abaño, MD (Philippine Journal of Ophthalmology)
Objective: To evaluate the efficacy, predictability, and safety of LASIK surgery using the Allegretto Wave Eye-Q excimer laser.